Reservoir Characterization and Volumetric Analysis of “Lee” Field, Onshore Niger Delta, Using 3D Seismic and Well Log Data - P. Adigwe; S. Inichinbia (Journal of Applied Sciences and Environmental Management)
Three dimensional (3D) seismic data, and a suite of four geophysical well logs from four wells located on the Lee field, Niger Delta were analyzed  using Petrel software for the aim of reservoir characterization and  volumetric analysis of the field. The objectives among others include  identification and delineation of the reservoirs and estimating the petrophysical parameters from the well logs available, generating time and depth structure maps of horizons from the seismic section, and a volumetric analysis in order to estimate hydrocarbon in place. The method adopted involves petrophysical analysis, structural analysis, static modelling, and volumetric analysis. Detailed petrophysical analysis revealed three reservoirs. Average Reservoir parameters such as effective porosity (0.17), gross thickness (86 m), hydrocarbon saturation (0.42), permeability (1215 mD) and net-to-gross (0.79) were derived from petrophysical analysis. The three reservoirs were classified using average results of petrophysical parameters. And based on these results, Reservoir 1 is the most prolific while Reservoir 3 is the least prolific within Lee field. Fault and Horizon interpretations were done using Petrel software which culminated in delivery of 3D structural map of the reservoirs. Structural, stratigraphic and Petrophysical models were developed and then integrated to produce a high resolution static model for Reservoir 1. The hydrocarbon in place shows that reservoir 1 is of appreciable thickness and areal extent. The volume of hydrocarbon originally in place was estimated to be 367,180,095.08 barrels of oil.